Genetics and management of inherited cancer predisposition 2 - Schiffman, Joshua (Henry Stewart Talks, 2016)
Hereditary cancer syndromes and genes, Li-Fraumeni Syndrome: germline TP53 mutation, Screening TP53 mutation carriers, Paraganglioma and other SDH-related tumors, SDH screening guidelines: “Utah Protocol”, VHL syndrome, Pediatric cancers that merit genetics evaluation, Comparative oncology, Canine cancer – breed predisposition, Elephant’s cancer (Peto’s paradox)